THE INFLUENCE OF CULTURE AND SELF-PERCEPTION ON THE MENTAL HEALTH CARE-SEEKING INTENTIONS OF COLLEGE STUDENTS - Jamadar, Shamin (East Carolina University, 2018)
Mental health issues are common among young adults, especially those attending colleges and universities. There has been a growing concern related to the number of unmet mental health concerns for students and the potential ramifications associated with this unmet need. Studies show that approximately 17% of college students experience a mental health concern, yet only 20% of those with a concern obtain mental health care services. One’s upbringing and background are known to influence decision making and are thus likely to play a role in decisions to seek mental healthcare; however, these norms can vary across cultures. In addition, depending on how one perceives the state of their own mental health, their intentions towards service utilization may be altered. The influence of culture and self-perception on intentions to seek mental health services were examined within this study. Results showed that students were more likely to recommend formal, professional, mental health treatments for their friend rather than themselves, even if symptoms were identical, X2 (1, N = 861) = 96.67, p < 0.001. However, the study did not indicate any significant relationship between background and likelihood to recommend formal treatment options, X2 (1, N = 422) = .549, p = .459, nor attitudes towards seeking professional psychological care, t(832) = -0.592, p = 0.554, d = 0.091. Identification of specific barriers preventing individuals from obtaining formal treatment warrants future research and will aid in development of future direction in how to provide care-services to diverse university populations.
Keywords: culture; self-perception; mental health; service utilization